Genome analysis of Clostridium botulinum type A by pulsed-field gel electrophoresis. - Lin, W J (1995)
Genomic DNA from type A Clostridium botulinum was digested with restriction endonucleases that cut at rare sites, and the large fragments were separated by pulsed-field gel electrophoresis. Of 15 restriction enzymes tested, MluI, RsrII, SmaI, NruI, KspI, NaeI, and XhoI generated satisfactory digestion patterns of genomic DNA of various C. botulinum strains, enabling the use of the method for genomic fingerprinting. The genomes of four group I (type A) C. botulinum strains examined had similar restriction patterns. However, each strain had unique digestion patterns, reflecting genotypic differences. The genome size of C. botulinum strain 62A was estimated to be 4,039 +/- 40 kbp from the summation of restriction fragments from MluI, RsrII, and SmaI digestions. Genes encoding proteins involved in the toxinogenicity of C. botulinum, including neurotoxin, hemagglutinin A, and genes for a temperate phage, as well as various transposon Tn916 insertion sites in C. botulinum 62A, were mapped by pulsed-field gel electrophoresis. The genes encoding neurotoxin and hemagglutinin A-1, were located on the same fragment in several cases, indicating their probable physical linkage. The macrorestriction analysis established here should be useful for genetic and epidemiological studies of C. botulinum.